ANALISIS FAKTOR YANG PALING BERHUBUNGAN DENGAN JUMLAH GIGI BERFUNGSI PADA LANSIA DI DESA MENGWI KABUPATEN BADUNG TAHUN 2015 - sagung putri (Jurnal Skala Husada : The Journal of Health, 2018)
ABSTRACT Generally, elderly has more experience physical setback, one of them is marked with loss teeth. The susceptible problem of dental and oral health which happened on elderly are dental caries and periodontal disease. In Indonesia, both diseases are the main cause elderly’s loss teeth.  Analysis of Factors Associated with the least amount of tooth Functioning in the Elderly in  Mengwi Badung 2015Research methods used in this research is descriptive method, and used 110 samples by Multi stage random sampling  technic. Based on data analysis bivariat dengan uji chi Square d uji regresi logistic. discussion of the research results, from 110 There was a significant correlation between the number of teeth that function in the elderly with age p = 0.000 (p 0.05). The education level of p = 0.000 (p 0.05). Economic status value of p = 0.000 (p 0.05). Concluded that the most influential factor is the level of education with a value of p = 0.000 (p 0.05) with OR 4.46,  (CI 95%  2.63 - 7.57). Suggestions addition of programs for oral health..                                                                                             Keywords: dental health, elderly, teeth function